Development of interdisciplinary projects as a pedagogical strategy to generate alternative solutions to problems in the environment (Memorias Sifored - Encuentros Educación UAN, 2021)
Strengthen the development of interdisciplinary research processes to generate alternative solutions to environmental problems.
Keywords: interdisciplinary research; pedagogy; problem solving; environment